EKSISTENSI MANILIAK AWAL BULAN OLEH TAREKAT SYATTARIYAH PARIAMAN - Soderi, Ridhokimura; darlius (UIN ALAUDDIN MAKASSAR, 2022)
The Maniliak Bulan tradition is an important thing for followers of theSyattariah Pariaman Order. This religious tradition is routinely carried out everyyear to welcome the holy month of Ramadan, and has become a symbol that hasbeen passed down from generation to generation since the Syattariyah Order beganto develop in Pariaman. In addition, the purpose of the research is to find out whatactivities are in the Maniliak Bulan tradition from followers of the Syatariahcongregation. Maniliak Bulan is a religious symbol that has meanings and valuescontained in this tradition, so that the followers of the Tariqa Syattariyah Pariamanmaintain this tradition. In this study, the author uses qualitative methods, namelydescriptive qualitative research with data analysis of interview and observationtechniques related to the problems of this research using the symbolic interpretivetheory approach by Geertz can be used to dissect cultural studies both in a societydirectly and in literary works. The reason for the existence of the Maniliak Bulanritual for religious and intellectual reasons and this tradition has meaning andvalues that encourage local people to maintain this tradition. These values are inthe form of religious values, spiritual values, intellectual values and economicvalues.